Antioxidative Effects of Muscovy Duck Meatballs with the Addition of Torch Ginger Flower Extract - Yudha Moningka; Chatarina Wariyah; Agus Slamet (International Journal of Technology, Food and Agriculture, 2026)
Muscovy duck meatballs are high-fat, wet foods that are susceptible to oxidation and microbial activity. Torch ginger flower extract (TFE) contains flavonoid compounds that can capture free radicals resulting from fat oxidation. The purpose of this study was to evaluate the antioxidative effect of Muscovy duck meatballs with the addition of TFE based on the changes in functional groups in meatballs. The materials used were male Muscovy duck meat  and torch ginger flowers. This study used a Randomized Block Design with variations in the meat/tapioca ratio (250g/37.5g; 250g/62.5g; 250g/87.5g) and the amount of ginger torch extract (8.35ml; 17.7ml; 28.05ml), as well as controls without and with sodium benzoate. Analysis included chemical criteria of the meatballs, antioxidant activity, identification of functional groups with FT-IR, and microbiological tests. The results showed that meatballs with more TFE added had higher antioxidant activity. Meatballs with a ratio of 250g/15g and 8.35 ml TFE exhibited antioxidant activity of 18.49±0.84%. Based on the FT-IR spectrum, the functional groups in the meatballs were the same as those in the torch ginger flower extract, namely -OH, aromatic C=C, and C-O. Implementing this functional meatball processing technology can provide safe food and reduce the risk of oxidative stress.